Precautionary construction management for sustainability - Mohamad Saiful Termizi, Mohamad Jani (2019)
The implementation for sustainability in the construction sector depends on the varying extents at global, national, regional, local, corporate and individual levels. The precautionary in sustainability development in all construction sector will brings a lot of benefits and functions to people nowadays and also for future generations used. To achieve sustainable construction, it is very important to balance the basic principles of sustainability i.e. environment, economic and social aspect together. The objectives of this study are review and identify the key principles of sustainability and promote positive impacts and minimizing negative impacts on economic, environmental and socials, to identify and design questionnaire framework related to precautionary construction management for sustainability, and to analysis the precautionary construction management for sustainability. The study is carried out through questionnaires. A total of 75 questionnaires were distributed and answered by respondents. The data were analyzed using Relative Importance Index. From the study, it was found that the purpose of the precautionary construction management is to preserve access to ecosystems services essential to health and wellbeing. In conclusion, respect people and their local environmental, and seek to minimize the adverse social impacts and maximize the positive social impacts of the project is the solution for the precautionary construction management for sustainability in construction sector.